Performing academic Masculinity in the Arctic: Sophus Tromholt and Roland Bonaparte's photographic accounts of Sámi peoples and Northern landscapes. Issue 4 (3rd September 2018) - Lien, Sigrid
ABSTRACT: This article discusses photographs of Sámi people produced in 1883 and 1884 by the Danish-Norwegian scholar and photographer Sophus Tromholt (1851–1896) and G. Roche, the expedition photographer of the French prince, Roland Bonaparte (1858–1924). While Tromholt's photographs have been understood as an example of how Sámi people were portrayed as individuals, and how they adapted the medium of photography for their own purposes, Roche/Bonaparte's anthropometric photographs are seen as the opposite, an attempt to document the typical, racial features of the Sámi population. Contrary to such an understanding, the article argues that there are more common features between these portraits and their contexts of production than earlier suggested. Inspired by Ali Behdad's discussions on the nature of orientalist photography, it neither sees Roche's/Bonaparte's nor Tromholt's photographic representations as entailing a binary visual structure between the Europeans as active agents, nor Sámi people as passive objects of representation. Furthermore, it suggests that there are common features to be observed in relation to their respective contexts of production, stressing how both Tromholt's and Roche's/Bonaparte's photographs of Sámi people and northern landscapes must be understood not only in the context of the photographic identity performances of the academic male subjects who represented them, but also in relation to the visual economy in which these representations were embedded. This involves a consideration of how travel narratives from pre-photographic Arctic expeditions played a mediating role for the later photographic practices in the Sámi areas.